Structural and spectroscopic properties of Nd3+:Y2Si2O7 phosphors - TAV, CUMALİ; ERDEM, MURAT (ELSEVIER SCI LTD, 2013)
Phosphors of alpha-Y2Si2O7 doped with Nd3+ ions were prepared using the sol gel technique. Nano-sized crystalline phosphor powders were obtained by annealing the dried gels at 960 degrees C. The crystallization properties of the phosphor powders were determined from their XRD patterns. The alpha-Y2Si2O7 phase was the only phase observed in all compositions. As the amount of amorphous SiO2 in the composition was increased, the crystalline sizes and the widths of the size distribution curves were found to decrease from 17.8 nm to 10.6 nm and from 15.6 nm to 12.2 nm, respectively. The spectroscopic properties of the powders were studied by measuring the luminescence and the decay patterns of the F-4(3/2) -> I-4(9/2) and F-4(3/2) -> I-4(11/2) transitions between 50 K and 310 K. No appreciable effect of the crystallite sizes on the average lifetime of the F-4(3/2) level was observed at temperatures below 100 K. The effect of temperature, however, becomes relevant above 100 K as the size of alpha-Y2Si2O7 nano-crystal becomes smaller. (C) 2013 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Nanophosphors; Sol-gel; Yittrium silicate; Life time; LASER; LUMINESCENCE